Kulliyah Al-Khams In The Code Of Ethics Of Social Media: An Analysis Of Maqashid Al-Syari’ah - Ichwansyah Tampubolon; Kholidah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Islamic law aims to safeguard five fundamental human needs: hifz ad-din (protection of religion), hifz an-nafs (protection of life), hifz al-aql (protection of intellect), hifz al-mal (protection of wealth), and hifz an-nasl (protection of lineage). In line with this, the social media code of ethics formulated by the government and Islamic organizations in Indonesia is expected to reflect the same principles. Norms and laws do not emerge arbitrarily but serve a purpose to ensure their practical benefits. Given the extensive influence of social media, this study examines the ethical framework through a philosophical lens, specifically using maqashid as-syari'ah as an analytical tool. As a literature study, this research relies on sources from academic references. The findings indicate that the formulation of the social media code of ethics aligns closely with the concept of maqashid as-syari'ah. The five essential protections—hifz ad-din, hifz an-nafs, hifz al-aql, hifz al-mal, and hifz an-nasl—are inherently embedded within its provisions. The use of prohibitive terms, such as “haram,” explicitly aims to maintain and protect kulliyah al-khamsiyah or ad-dharuriyah al-khamsiyah from negative things or harm caused by social media users.